Peranan Psikotes Bagi Peserta Didik SMP Dan SMA - Manufandu, Tonny Silas (Universitas Cenderawasih, 2015)
The meaning of The Phsycological test in this paper is a set of test instruments to measure various aspects of phsycological usual, suchas intelligence, interest, personality, and so the others have been treated so that it has sufficient validity and rehabilitation or quite high and usually already in standarsize. From the phsycological test mean, we can see the two are important, namely the validity and rehabilitation. The meaning of validity is statue or correspondence between the measurement results with what you want in the measure, while rehabilitationis constancy in the measurement.